Dampak Maraknya Penggunaan Bank Emok Pada Kalangan Ibu Rumah Tangga Di Kampung Leuweung Gede Kota Cimahi - Neng Santi Anggraeni; Ageng Saepudin Kanda S (Jurnal Manajemen Riset Inovasi, 2024)
One of the problems that humans face in everyday life is the economy, especially in terms of meeting needs. To survive, humans have to meet all their complex needs. Because rural people often have economic difficulties, they are the most involved in Emok Bank. An Emok Bank is a type of bank that lends money to people by visiting customers in person by sitting upright with both legs bent backwards. An Emok Bank transaction system is done by sitting licensed in certain places, like the terrace of a client's house. Qualitative research is research that produces descriptive data that are written or oral words of people and behaviour that can be observed. The Emok Bank has made the public worried about the high interest rates and the liability system used in the shares. As a result, many communities, especially households, are plunged into problems arising from paying difficulties. Often, loans from this Emok Bank are used to pay off debts to other Emok Banks. Economic circumstances make a householder dependent on a mother's bank. The existence of an Emok Bank has led to bad behavior against the households in the village of Leuweung Gede, most of them being borrowers to an emoc bank that borrows more than one bank.